Sporothrix humicola (Ascomycota: Ophiostomatales) – A soil-borne fungus with pathogenic potential in the eastern quoll (Dasyurus viverrinus) - Anne Nesseler; Nicole Schauerte; Christina Geiger; Kerstin Kaerger; Grit Walther; Oliver Kurzai; Tobias Eisenberg (Medical Mycology Case Reports, 2019)
The genus Sporothrix contains both species pathogenic to humans and animals as well as environmental fungi. S. humicola, a member of the latter S. pallida clade, has previously been reported only from soil. We have isolated this dimorphic fungus from multiple cutaneous lesions in two endangered marsupials native to Tasmania. Clinical appearance resembled cutaneous sporotrichosis, highlighting the principle pathogenic potential. Identification was based on partial ITS, β-tubulin and calmodulin gene sequencing. Keywords: Sporothrix humicola, Eastern quoll, Dasyurus viverrinus, Dermatomycosis, MALDI-TOF MS